The Influence of the Corporate Venture Capital on the Innovative Development of the Russian Economy - L. G. Pashtova (Финансы: теория и практика, 2021)
The author examines the place and role of corporate venture funds, the state of the venture capital marketin Russia, and the impact of venture financing on the innovative activity of corporations, in particular, on theinnovative development of the economy as a whole. The purpose of the study is to provide an economic assessment  of the importance of using corporate venture capital for the innovative economy of the Russian Federation. The author applies methods of statistical, financial, and logical analysis. The study covers the period 2013–2020 and is based on the analysis of data from international organizations, analytical centers, mass media, official data sources of the Government of Russia, and the Central Bank of the Russian Federation. The author reviewed the literature and analyzed the practice of corporate venture capital funds to understand investment in innovation in Russia and around the world. The article analyses the history of the emergence and development of corporate venture funds in Russia and other countries and provides an assessment of the innovation activity of corporations and the Russian state. The theoretical aspects of corporate venture funds, the dynamics of the development of the innovative activity, and the venture market in Russia are considered. The author makes a conclusion about the need for state regulation of the processes of financing scientific and technological development and the effective use of market instruments, such as corporate venture funds.